Information Technology Evaluation: Review and Criticism - Budhi Kristianto (AITI, 2016)
Nowadays almost all aspects in human life influenced by information technology. Almost all devices used by human were controlled by computer systems. Lot of investments were made, with not much of evaluation and feedback of the gained benefits were reported. This study tries to figure out how Information Technology is evaluated, approaches that been done, and critics for continually improvement. Review is started with IT-paradox, followed by IT-success, IT-values, IT-evaluations, IT-adoptions, and IT-management. Manuscript is ended with critics and discussion, implications, and conclusion.